Association of Fatty Acid Ethyl Esters in Meconium and Cognitive Development during Childhood and Adolescence - Min, Meeyoung O. (J Pediatr, 2015)
OBJECTIVE: To examine associations between amounts of fatty acid ethyl esters (FAEEs) in meconium and cognitive development in school aged children exposed to alcohol and drugs in utero. STUDY DESIGN: A secondary analysis of a prospective cohort of children, primarily African-American and of low socioeconomic status, that were recruited at birth. FAEEs were quantified with gas chromatography using a flame ionization detector. Meconium was analyzed for FAEEs in 216 newborns. 191 of these infants were assessed for IQ at ages 9, 11, and 15 years using the Wechsler Intelligence Scales for Children-Fourth Edition (WISC-IV). RESULTS: Longitudinal mixed model analyses indicated that, controlling for maternal and child covariates, higher concentrations of FAEEs (ethyl myristate, ethyl oleate, ethyl linoleate, ethyl linolenate) were associated with lower WISC-IV Verbal Comprehension Index (VCI), Working Memory Index (WMI), and Full Scale IQ (FSIQ). Associations of FAEEs with VCI, WMI, and FSIQ did not vary over time. No association of FAEEs with Perceptual Reasoning and Processing Speed Indices were found. CONCLUSION: Elevated levels of FAEEs in meconium are potential markers for identifying newborns at risk for poor cognitive development related to prenatal alcohol exposure.